Distribution and diversity of Fusarium species associated with grasses in ten states throughout Peninsular Malaysia - Mohd Zainuddin, Nur Ain Izzati; Mohd Sidique, Siti Nordahliawate; Ismail, Nor Azliza; Salleh, Baharuddin (Seameo Biotrop, 2009)
Fusarium is one of the important genera associated with grasses as saprophytes, endophytes and pathogens. A study was carried out on distribution and diversity of Fusarium species associated with two groups of grasses in 10 states throughout Peninsular Malaysia i.e.agricultural grasses (Oryza sativa and Saccharum officinarum) and non- agricultural grasses (Axonopus compressus, Centhotheca lappacea, Chloris barbata, Crysopogon aciculatus, Cyanadon dactylon, Dactyloctenium aegyptium, Digitaria ciliaris, Echinochloa colona, Eleusine indica, Eragrostis amabilis, Eragrostis malayana, Eragrostis uniloides, Ischaemum magnum, Panicum brevifolium, Panicum millaneum, Panicum repens, Paspalum commersonii, Paspalum conjugatum, Paspalum orbiculare, Pennisetum purpureum, Sacciolepis indica, Sporobolus diander and Sporobolus indicus). A total of 474 isolates were single-spored and identified by morphological characteristics. F. semitectum was frequently isolated (23.6%), followed by F. sacchari and F. fujikuroi with 15.4% and 14.6%, respectively. The other nine species were F. solani (10.3%), F. proliferatum (8.9%), F. oxysporum (7.4%), F. subglutinans (6.5%), F. equiseti (5.5%), F. verticillioides (3.4%), F. compactum (2.5%), F. chlamydosporum (1.1%) and F. longipes (0.8%). Based on the Shannon-Weiner Index, F. solani was the highest (H' = 2.62) isolated from grasses. Species of Fusarium from O. sativa were widely diverse with 11 species, followed by non- agricultural grasses with nine species and S. officinarum with only six species.